Public Relations Strategies for Addressing Emerging Cybersecurity Threats in Nigeria’s Digital Economy - Suleiman Garba PhD; Kelvin Inobemhe (LSPR Institute of Communication & Business, 2026)
The rise of Nigeria’s digital economy has been accompanied by escalating cybersecurity threats, imperiling digital transactions and eroding public trust, particularly within the vital Financial Technology (FinTech) sector. This study investigated the effectiveness of public relations (PR) strategies in countering these threats, with a precise focus on proactive approaches to enhance cybersecurity awareness and resilience in Nigeria’s FinTech landscape, an area underexplored compared to technical cybersecurity research. Integrating the technology acceptance model (TAM) and situational crisis communication theory (SCCT), the study examined how PR shapes stakeholder perceptions and adoption of security measures, such as two-factor authentication, while guiding crisis responses to maintain trust. Adopting a qualitative approach, the study analysed secondary data from academic articles, industry reports, and Nigerian FinTech case studies, enriched by primary data from expert interviews with four Nigerian PR and four cybersecurity experts, to map the current threat landscape and PR efficacy. Findings revealed that proactive PR emphasising transparency, timely communication, and educational campaigns outperforms reactive strategies in fostering trust and reducing incident frequency, despite the barriers posed by digital illiteracy and misinformation, exemplified by a 2023 bank collapse rumour. Resource constraints further challenge implementation. The study recommended a proactive, integrated PR framework, contrasting it with reactive efforts, and proposes a national regulatory framework led by the Central Bank of Nigeria (CBN) and Nigerian Communications Commission (NCC) to adopt clear, multilingual communication, forward-thinking PR strategies, nationwide workshops, coordinated crisis communication, disaster plans with simulations, and partnerships with third parties to establish a credible regulatory structure, thereby strengthening digital resilience